1996
DOI: 10.1177/001979399605000104
|View full text |Cite
|
Sign up to set email alerts
|

Employee Stock Ownership and Corporate Performance among Public Companies

Abstract: This study compares the corporate performance in 1990/91 of two groups of public companies: those in which employees owned more than 5% of the company's stock, and all others. The results of the analysis, which looks at profitability, productivity, and compensation, are consistent with neither negative nor highly positive views of employee ownership, but where differences are found, they are favorable to companies with employee ownership, especially among companies of small size. The circumstances in which emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 12 publications
4
157
0
6
Order By: Relevance
“…The study finds mixed effects on performance -while worker-owners display higher job satisfaction and motivation, they are not more productive than workers who do not own equity in their companies. Blasi, Conte, and Kruse (1996) use corporate data for the United States to find that employee ownership is associated with improved firm performance only in small-size companies. We use the available evidence to argue that employees, like small shareholders, may be less able (and face little incentive) to monitor firm restructuring.…”
Section: Ownershipstructureandfirmrestructuringmentioning
confidence: 99%
“…The study finds mixed effects on performance -while worker-owners display higher job satisfaction and motivation, they are not more productive than workers who do not own equity in their companies. Blasi, Conte, and Kruse (1996) use corporate data for the United States to find that employee ownership is associated with improved firm performance only in small-size companies. We use the available evidence to argue that employees, like small shareholders, may be less able (and face little incentive) to monitor firm restructuring.…”
Section: Ownershipstructureandfirmrestructuringmentioning
confidence: 99%
“…Empirical evidence from Frye (2004) [21]suggested that companies with higher percentage of ESOs render greater performance. Blasi et al (1996) [3]established that firms adopting stock options in the same industry and of same size during 1990 exhibited similar levels of profitability, however significantly higher growth in return on assets, price/earnings ratio and profit margin was noted for adopters in comparison to the non-adopters during 1980 -1990. The study therefore, documented that small companies exhibited a positive relationship between employee stock option adoption and profitability growth but could not find any strong association between stock options and productivity.…”
Section: Arguments In Favor Of Issuance Of Esopsmentioning
confidence: 97%
“…Employee stock ownership plans-"ESOPs"-are usually organized so as to minimize worker participation in management decisions. (Kelso & Hetter 1967, Kelso & Adler 1958, Blasi & Kruse 1991, Blasi, Conte and Kruse 1996 Thus, worker ownership based on these plans are not per se within the scope of this essay. Even so, "actual [worker cooperatives] are in fact quite heterogenous."…”
Section: Cooperation Ownership and Controlmentioning
confidence: 98%